2022
DOI: 10.1186/s12863-022-01091-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for related traits of stalk lodging resistance using genome-wide association studies in maize (Zea mays L.)

Abstract: Background Stalk lodging is one of the main factors affecting maize (Zea mays L.) yield and limiting mechanized harvesting. Developing maize varieties with high stalk lodging resistance requires exploring the genetic basis of lodging resistance-associated agronomic traits. Stalk strength is an important indicator to evaluate maize lodging and can be evaluated by measuring stalk rind penetrometer resistance (RPR) and stalk buckling strength (SBS). Along with morphological traits of the stalk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We have successfully identified and validated a middensity marker set for routine genotyping of pearl millet lines and its usefulness for various genomic studies. By Genetic diversity is the basis of evolution (Hughes et al, 2008) and provides the raw material for evolution of natural selection (Nevo, 1988;Zhang et al, 2022). Intraspecific genetic variation is the basis and most basic level of biodiversity (Pauls et al, 2013), and it is important for the evolution and conservation of species (Ellegren and Galtier, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We have successfully identified and validated a middensity marker set for routine genotyping of pearl millet lines and its usefulness for various genomic studies. By Genetic diversity is the basis of evolution (Hughes et al, 2008) and provides the raw material for evolution of natural selection (Nevo, 1988;Zhang et al, 2022). Intraspecific genetic variation is the basis and most basic level of biodiversity (Pauls et al, 2013), and it is important for the evolution and conservation of species (Ellegren and Galtier, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Zm00001d014449 is associated with LHP1 gene, which is involved in vascular bundle synthesis, and is important to maintain the specificity of cell and tissue structure; Zm00001d010201 expresses MYB6 transcription inhibitors related to the secondary wall. Previous studies [ 4 , 27 ] have confirmed that the MYB transcription factor family can be used as stalk strength related genes for in-depth research; Zm00001d029860 participates in the metabolism of 3-hydroxyisobutyl CoA hydrolase, which affects cell wall synthesis through biological processes such as lipid transport and metabolism. Further in-depth research is needed in the next step.…”
Section: Discussmentioning
confidence: 99%
“…In particular, Zm00001d014449 is associated with LHP1 gene, which is involved in vascular bundle synthesis, and is important to maintain the speci city of cell and tissue structure, Zm00001d010201 expresses MYB6 transcription inhibitors related to the secondary wall. Previous studies [4,23] have con rmed that the MYB transcription factor family can be used as stalk strength related genes for indepth research, Zm00001d029860 participates in the metabolism of 3-hydroxyisobutyl CoA hydrolase, which affects cell wall synthesis through biological processes such as lipid transport and metabolism.…”
Section: Analysis Of Genes Associated With Corn Stalk Related Traitsmentioning
confidence: 99%